Improving The Quality of The Yoghurt With The Addition of Honey - Nugroho Krisnaningsih, Aju Tjatur; Yulianti, D. L. (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
Yoghurt is one of the functional food products with the potential to be developed and needed by the community. This research aimed to improve the quality of the yoghurt with theaddition of honey. The study employed Completely Randomized Design with four treatments: 2, 4, 6,8, and 10% honey levels. The data were analyzed by aoa folloed  Dua’s Multiple RageTest if there were significantly effects.  The results showed that the different honey levels gavesignificantly difference effect (P<0.01) on the crude protein content, but not significant (P>0.05) onPH. The highest adding (10%) of honey in yoghurt gave the best result with the crude protein of4.34% and PH at 4.0. The sensory evaluation result showed significant differences (P<0.05) ontexture and aroma, but not significant (P>0.05) on color and taste. Level of 10% of honey inclusionhad the highest overall acceptability score.Key Words: Yoghurt, Honey, Crude Protein, PH, Organoleptic Analyses